ANALISIS PEMANFAATAN METODE DEMONSTRASI DALAM MEMBERIKAN MOTIVASI BELAJAR PADA ANAK USIA 5-6 TAHUN - Nurjumawati, Nismah Murni; Lukmanulhakim, Muhammad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe purpose of this research is to describe Analysis of Utilization of Demonstration Method in Giving Motivation Learning In Child Age 5-6 Year in Kindergarten Pertiwi Sanggau Regency. The method used is descriptive with qualitative research form. The subjects of the study were classroom teachers and group 1 companion teachers, and 5-6 year old children in group B 1 in TK Pertiwi sanggau district. Data collection techniques used interview techniques, and documentation. In testing the validity of the data the researchers used the technique of triangulation.From general research results can be edited. Analysis of Utilization of Demonstration Methods in Giving Motivation Learning In Children Aged 5-6 Years in Kindergarten Pertiwi Sanggau District conducted by teachers is quite good. Learning methods in providing teacher assistance is done in accordance with the existing stages, the implementation of learning methods in providing motivation to learn, teachers invite children to pay attention to teachers, then do activities with the method of demonstration, taking themes and activities with demonstration methods in the accompanying the original media.Evaluation method to provide teacher learning aid for 5-6 year students, the teacher reflects by asking the children and learning the children in the learning with the method of polishing done by the teacher is good. Teachers should be more often to do learning using agar-agar methods can increase the motivation of children.Keywords: utilization of demonstration methods, motivation to learn child